EPIDEMIOLOGY OF UNDERFIVE MALNUTRITION : SEX DIFFERENTIAL IN HEALTH CARE AND NUTRITIONAL STATUS (UNDERFIVE MALNUTRITION) - BANERJEE, A (Med J Armed Forces India, 1998)
Under five children of defence personnel attending an immunisation clinic in a peace station over a three year period were screened for malnutrition and hemoglobin status. One thousand two hundred and forty eight underfives attended the clinic, out of which 703 (56.33%) were boys and 545 (43.67%) were girls. Girls showed a greater prevalence of various grades of malnutrition (28.9%) compared to boys (21.9%), (p=0.01335458). Mean hemoglobin level was marginally lower in girls at 10.8 gm per cent, compared to boys at 11.2 gm per cent (p=0.000001). Overall 25 per cent of underfives were suffering from various grades of malnutrition which is much lower than the national malnutrition rate of 63 per cent among underfives.